HOTS: Hotel Occupancy Tracker in Sabah - Melissa Tatiana, Lupang (Universiti Malaysia Sarawak (UNIMAS), 2019)
HOTS: Hotel Occupancy Tracker in Sabah is a web-based system designed for Sabah Tourism Board to handle a large amount of occupancy surveys from various hotels around Sabah. The main purpose of this project is to convert the current system of gathering and managing the hotel occupancy surveys. This system will provide an online occupancy forms for the hotel administrator to easily fill in the form and submit online. From this, Sabah Tourism Board is able to gather all the occupancy surveys in a shorter period of time as well as getting information of tourists’ visits in Sabah. In conjunction, Sabah Tourism Board will be able to monitor the state tourism activity by keeping track the amount of tourists visit in Sabah yearly as well as the performance of the hotels. Other than that, this system also provides a hotel information form for hotel administrator to update their hotel information. The system will be able to provide a hosting dashboard for hotel administrators to monitor the occupancy activity announcement regarding their hotel in one page. Furthermore, the methodology used to develop this project is Rapid Application Development (RAD).